The Role of Job Satisfaction in Mediating Quality of Work Life, Work Motivation, and Leadership on Employee Performance Case Study at Fave Rembang Hotel - Ariefiantoro, Teguh; Raharja, Edy; Suharnomo, Suharnomo (JURNAL BISNIS STRATEGI, 2025)
The performance of a company is determined by the condition and behavior of its employees. The phenomenon that often occurs is that the performance of a company that has been so good can be disrupted, either directly or indirectly by various employee behaviors that are difficult to prevent from occurring. Human resources have a very important role in the organization, because human resources cause other resources to function and run. So important is the role of human resources, this factor is what determines the back and forth of the organization. The population in this study were employees of Fave Hotel Rembang. The sampling technique used in this research is non-probability sampling method. The results showed that the variables of Quality of Work Life, Work Motivation, Leadership and Job Satisfaction had a positive and significant effect on Employee Performance of Fave Hotel Rembang. The analysis methods used are Convergent Validity, Discriminant Validity, Composite Reliability and Inner Model. From the results of the research conducted, it shows that Work Motivation has a positive effect on employee performance, Quality of Work Life variables have a positive effect on employee performance, Leadership variables have a positive effect on employee performance, Work Motivation variables have a positive effect on job satisfaction, Quality of Work Life variables have a positive effect on job satisfaction, and Leadership variables have a positive effect on job satisfaction.